2012
DOI: 10.1074/jbc.m112.350884
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-associated Box Repressor Domain Can Induce Reversible Heterochromatization of a Mouse Locus in Vivo

Abstract: Background:The KRAB module mediates ectopic and drug-controllable transcriptional repression. Results: Targeting of KRAB to a mouse gene body results in reversible heterochromatization and gene silencing in adult and embryonic cells. Conclusion: KRAB binding to gene bodies does not induce stable DNA promoter methylation as previously thought. Significance: These proof-of-principle experiments provide the basis for the development of novel KRAB-based tools in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…This irreversible silencing was due to KRAB-induced de novo DNA methylation of the promoter ( 13 ). However, a recent study suggested that tethering of KRAB to an endogenous gene body does not contribute to irreversible gene silencing, even under the same circumstances as previously described, as KRAB binding to gene bodies did not induce stable DNA promoter methylation ( 14 ). It is worthy to note that in these experiments, tetO-controlled GFP was inserted into the genome using a lentivirus vector, and in some cases, KAP1 has silenced retroviruses in embryonic stem (ES) cells and early embryos ( 15 18 ).…”
Section: Introductionmentioning
confidence: 76%
“…This irreversible silencing was due to KRAB-induced de novo DNA methylation of the promoter ( 13 ). However, a recent study suggested that tethering of KRAB to an endogenous gene body does not contribute to irreversible gene silencing, even under the same circumstances as previously described, as KRAB binding to gene bodies did not induce stable DNA promoter methylation ( 14 ). It is worthy to note that in these experiments, tetO-controlled GFP was inserted into the genome using a lentivirus vector, and in some cases, KAP1 has silenced retroviruses in embryonic stem (ES) cells and early embryos ( 15 18 ).…”
Section: Introductionmentioning
confidence: 76%
“…With respect to repression, it has been shown in embryonic stem cells that KRAB (as part of SKD) can indirectly induce de novo DNA methylation via recruiting its cofactor, KAP1 (43). In addition, KRAB/KAP1 can spread H3K9me3-containing heterochromatin in adult and embryonic stem cells (44). Despite these reported functions of KRAB in epigenetic regulation, KRAB-induced repression is generally considered to be transient.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic TAL DBDs (T-DBDs) can be appended at either their C-or N-termini with effector domains conferring function in mammalian cells -for example the KRAB repressor domain 15,23 . In both native and artificial TFs, KRAB domains recruit the KAP1 co-repressor and, in turn, endogenous enzymatic complexes that methylate histones and DNA and trigger focal heterochromatin formation [23][24][25][26][27][28] .…”
Section: Resultsmentioning
confidence: 99%